On-chip narrowband thermal emitter for filter-free gas sensing - Tao, Xingyu (Nanyang Technological University, 2020)
Gas sensing technology has become more significant because of its widespread and common application in many areas, especially poisonous gas sensing and environmental analysis. Productive light source perfect to integral Complementary metal oxide semiconductor (COMS) innovation are key segments for minimal effort [1], conservative mid-infrared gas sensing frameworks. However, most gas sensors on the market are based on nondispersive infrared technology (NDIR) which is not efficient because the lack of integral COMS. In this project, we propose a new optical gas sensing system by combining a on-chip narrowband warm light source for the mid-infrared wavelength with a flat Metalens in micron thickness. Here, we design and demonstrate Metalenses in the mid-infrared wavelength by patterning a group of germanium nano fins. The Metalenses operating at 3-6μm are simulated by using finite-difference time-domain (FDTD) software.